2022
DOI: 10.3389/fncel.2022.1054956
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-dependent apoptosis induces reactivation and gliogenesis of astrocytes in adult mice

Abstract: Astrocytes play an important role in increasing synaptic plasticity, regulating endogenous homeostasis, and contributing to neuroprotection but become overactivated or apoptotic in persistent neuroinflammatory responses or pathological conditions. Although gliogenesis under these conditions may be essential for neuronal protection, much remains unknown. Here, we generated new conditional transgenic mice (cTg) that can induce apoptosis via Cre-dependent active caspase-3 (taCasp3-2A-TEVp) without pathological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, our results showed that the intensity of GFAP fluorescent decreased in the young unvaccinated infected groups, possibly due to the infection of astrocytes by neurotropic influenza viruses, which has been previously reported to lead to apoptosis ( Pei et al, 2014 ; Ng et al, 2018 ; Hosseini and Korte, 2023 ). In this context, it has also been shown that apoptosis of astrocytes in the hippocampus with activated caspase-3 leads to a sharp decrease in astrocyte number ( Kim et al, 2022 ). Moreover, this evidence is consistent with previous findings that GFAP was downregulated during acute corneal HSV-1 infection and upregulated in the late stage, suggesting that GFAP may play some role during corneal HSV-1 infection ( Zhao et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, our results showed that the intensity of GFAP fluorescent decreased in the young unvaccinated infected groups, possibly due to the infection of astrocytes by neurotropic influenza viruses, which has been previously reported to lead to apoptosis ( Pei et al, 2014 ; Ng et al, 2018 ; Hosseini and Korte, 2023 ). In this context, it has also been shown that apoptosis of astrocytes in the hippocampus with activated caspase-3 leads to a sharp decrease in astrocyte number ( Kim et al, 2022 ). Moreover, this evidence is consistent with previous findings that GFAP was downregulated during acute corneal HSV-1 infection and upregulated in the late stage, suggesting that GFAP may play some role during corneal HSV-1 infection ( Zhao et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%